1984
DOI: 10.1177/0148607184008002187
|View full text |Cite
|
Sign up to set email alerts
|

Intrajejunal Feeding: Development and Current Status

Abstract: Techniques of jejunostomy were established in surgical practice by the turn of the century. They were mainly used to administer normal food for the palliation of advanced gastric cancer. Standard postoperative intravenous fluid therapy did not begin in earnest until the late 1930's and did not become routine until the late 1940's because of pyrogens, fear of fluid overload, and commercial nonavailability. For most gastric procedures performed from 1900 until 1940, postoperative treatment consisted of nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…An alternative to TPN in patients who un¬ dergo upper-gastrointestinal-tract or pancreaticobiliary procedures is enterai nutrition administered by needlecatheter jejunostomy (NCJ).3 The use of enterai nutrition has the advantages of avoiding the low, but finite, incidence of septic and technical complications of central venous catheters as well as decreasing cost. 4 Controversy remains as to the optimal route of administration of nutrients.…”
mentioning
confidence: 99%
“…An alternative to TPN in patients who un¬ dergo upper-gastrointestinal-tract or pancreaticobiliary procedures is enterai nutrition administered by needlecatheter jejunostomy (NCJ).3 The use of enterai nutrition has the advantages of avoiding the low, but finite, incidence of septic and technical complications of central venous catheters as well as decreasing cost. 4 Controversy remains as to the optimal route of administration of nutrients.…”
mentioning
confidence: 99%
“…Cole et al have clearly demonstrated delayed gastric emptying and reflux of enteral feedings followed by aspiration with the use of a PEG [4]. Intrajejunal feeding appears to offer a reasonable approach to prevent aspiration by infusing the feeding distal to the pylorus [8,10,17,19]. Ryan and Page [19] concluded that "intrajejunal feeding negated the risk of gastroesophageal reflux and aspiration pneumonia."…”
Section: Discussionmentioning
confidence: 99%
“…Intrajejunal feeding appears to offer a reasonable approach to prevent aspiration by infusing the feeding distal to the pylorus [8,10,17,19]. Ryan and Page [19] concluded that "intrajejunal feeding negated the risk of gastroesophageal reflux and aspiration pneumonia." Nevertheless, aspiration has occurred following surgically placed jejunostomies as reported by Adams et al [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers assert that continuous infusion of formula into the stomach leads to bacterial overgrowth, upwards migration, and subsequent respiratory infection. Feeding distal to the pylorus is believed to reduce the risk of gastroesophageal reflux and subsequent pneumonia [ 108]. Jejunostomy feedings have been successfully used in the nutritional support of patients with cystic fibrosis [109,110], a population at high risk for gastroesophageal reflux.…”
Section: Nutrition Supportmentioning
confidence: 99%